DISEÑO E IMPLEMENTACIÓN DE UN SISTEMA DE INSONORIZACIÓN EN LOS AMBIENTES Y ESPACIOS CRÍTICOS INDUSTRIALES EN LAS PLANTAS DE PRODUCCIÓN DE AZULEJOS Y PISOS DE C.A ECUATORIANA DE CERÁMICA - Peñafiel Campoverde., Rosa Verónica (2011)
This research presents the theoretical framework as a basis for understanding different concepts of noise, its complications, and the hearing protection to be used. Information on the ear and how it works and common causes of damage are also included. The evaluation methodology determines whether the exposure level are acceptable or not by the noise assessment which includes plants and Tile Floors. The next step is noise maps to find the critical points of each plant To make measure the dimensions of each of the motors, fans, bands, etc. To undertake the design of the booths. To apply different methods of noise control, such as cockpit design of sound insulation in the critical points, or the use of personal protective devices to reach the desired level of reduction. Finally, we present a sound insulation system and its control measures. And a hearing conservation program for preventing hearing disability as a result of exposure to noise at work.